Improving Students’ Speaking Ability Through Islamic Movies as a teaching Media - Ari Andre Rianyansa; Syafryadin; Iis Sujarwati (English Education Study Program Faculty of Teacher Training and Education, 2024)
Speaking is a language skill that has to be mastered by students in learning a language because the objective of learning a language is communication. Islamic movies are a kind of media that the teacher can use to teach speaking. Islamic movie or Islamic animation movie is movie that has the content about the Islamic value and has the advantage to propagate Islamic information or spread da’wah to the students. Islamic movies contain speaking that relates to the illustrations, which can help students improve their speaking ability quickly. The descriptive-qualitative research approach was applied in this study. The participants of this study were 20 tenth grade students from Hidayatul Mubtadi’ien Islamic boarding school Bengkulu city in the academic year 2023-2024. To obtain data, the researcher employed a speaking test, observation, field notes, and interview. According to the results, there was a significant increase in students' ability in the form of an increase in English speaking and also in their motivation to improve the speaking contained in the Islamic movies. Additionally, the researcher saw several factors that influenced the improvement of students' speaking ability by using the media in the form of Islamic movies. The factors were that Islamic movies influenced the students' motivation and Islamic movies influenced the students’ activeness in the learning process. The researcher noticed that students became more enthusiastic and excited during the teaching and learning process by applying this medium. Therefore, the researcher suggests that Islamic movies can be used as supplement of teaching media, especially in order to improve speaking ability as well as students' interest in speaking.